2011
DOI: 10.1037/a0024279
|View full text |Cite
|
Sign up to set email alerts
|

Temporal processing of emotional stimuli: The capture and release of attention by angry faces.

Abstract: The anonymous reviewers are thanked for their helpful comments, suggestions and advice concerning this manuscript; as is James Elander. AbstractNeuroimaging data suggest that emotional information, especially threatening faces, automatically capture attention and receive rapid processing. Whilst this is consistent with the majority of behavioural data, behavioural studies of the attentional blink (AB) additionally reveal aversive emotional first target (T1) stimuli are associated with prolonged attentional en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 36 publications
6
43
0
Order By: Relevance
“…The fact that angry faces had a lesser effect on T2 target detection might, at first, appear to conflict with the work of Maratos (2011) who showed that angry expressions in the T1 target position attenuate T2 target detection. Indeed, since fearful and angry expressions are at once interesting, arousing, and negatively valenced, it would be reasonable to expect that both of these expressions would affect attention in similar ways (Davis et al, 2011; Shapiro, Raymond, Arnell, 1997; Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The fact that angry faces had a lesser effect on T2 target detection might, at first, appear to conflict with the work of Maratos (2011) who showed that angry expressions in the T1 target position attenuate T2 target detection. Indeed, since fearful and angry expressions are at once interesting, arousing, and negatively valenced, it would be reasonable to expect that both of these expressions would affect attention in similar ways (Davis et al, 2011; Shapiro, Raymond, Arnell, 1997; Smith et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…Maratos (2011) used schematic faces in an attentional blink paradigm to show that negatively valenced expressions (i.e. angry) presented in the T1 position produced a greater blink than either happy or neutral faces.…”
mentioning
confidence: 99%
“…Thus there appears to be a natural bias to prioritise attention and processing resources toward threatening rather than positive or rewarding stimuli (e.g. Simione et al, 2014;Maratos, 2011;LeDoux, 2003;Ohman, Lundqvist & Esteves, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…Beyond the results of experiments that have manipulated spatial frequency information it is not clear how the ASAP account might explain the effects of emotional stimuli on RT and accuracy in experiments that have neither controlled for nor manipulated the presence of spatial frequency information. For facial expressions specifically, experiments have reported a diverse set of findings including: 1) reductions in target detection accuracy following expressions presented in rapid sequence of images (de Jong, Koster, van Wees, & Martens, 2010;Maratos, 2011;Peers & Lawrence, 2009;Sigurjónsdóttir, Sigurðardóttir, Björnsson, & Kristjánsson, 2015;Stebbins & Vanous, 2015;Vermeulen, Godefroid, & Mermillod, 2009) 2) increased target detection accuracy following fearful compared to angry expressions (Taylor & Whalen, 2014) 3) faster visual search for complex images following the presentation of a fearful face (Becker, 2009;Quinlan & Johnson, 2011) 4) slower RTs when fearful and other expressions are presented as task-irrelevant distractors (Berggren, Richards, Taylor, & Derakshan, 2013;Fox et al, 2002;Georgiou et al, 2005;Gupta, Hur, & Lavie, 2016;Hodsoll et al, 2011;Van Dillen & Koole, 2009) and 5) faster RTs for neutral probes following in the same location as a threat-related expression (e.g., Bradley, Mogg, Falla, & Hamilton, 1998). Although it is difficult to summarize the interpretation for each result (for reviews see; Mogg & Bradley, 2016;Yiend, 2010) a common interpretation of both RT and accuracy effects in these studies is that emotion biases the competition for limited resourcesa competition that emotion stimuli are, as the result of evolutionary pressures, predisposed to win or influence.…”
Section: Affecting Speed and Accuracy In Perceptionmentioning
confidence: 99%